Output gaps and robust monetary policy rules - Roberto M. Billi (Sveriges Riksbank, 2012)
Policymakers often use the output gap, a noisy signal of economic activity, as a guide for setting monetary policy. Noise in the data argues for policy caution. At the same time, the zero bound on nominal interest rates constrains the central bank's ability to stimulate the economy during downturns. In such an environment, greater policy stimulus may be needed to stabilize the economy. Thus, noisy data and the zero bound present policymakers with a dilemma in deciding the appropriate stance for monetary policy. I investigate this dilemma in a small New Keynesian model, and show that policymakers should pay more attention to output gaps than suggested by previous research.
Keywords: E52; E58; 330; output gap; measurement errors; monetary policy; zero lower bound; Geldpolitik; Zinsstruktur; Neukeynesianische Makroökonomik; Taylor-Regel; Theorie